FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD BATARA SIANG PANGKEP - Nurul Sukmawati; Rusli Taher; Nurhikmah Nurhikmah (Stikes Graha Edukasi Makassar, 2020)
Objective: Asphyxia neonatorum is a condition where the baby cannot breathe spontaneously and regularly after birth. This is caused by fetal hypoxia in the uterus and hypoxia is related to factors that arise in pregnancy, childbirth or soon after the baby is born. Method: The study was conducted in November 2018 at Batara Siang Pangkep Regional Hospital. The population in this study was all 64 newborns who received a sample of 39 people with a purposive sampling technique. Results: The results showed that there was a relationship between premature rupture of membranes and the incidence of asphyxia. The results showed that there was a relationship between bad labor and the incidence of asphyxia. Suggestion: It is recommended to increase counseling and good antenatal supervision so that the incidence of asphyxia can be suppressed. It is expected that every pregnant woman can take advantage of health facilities both in hospitals, health centers or at the nearest midwife